THE URGENCY OF UNDERSTANDING DIGITAL LITERACY IN THE FLOW OF DIGITALIZATION OF COMMUNICATION AND INFORMATION - Ridho, Ali; Sujud, Mohammad; S.M. Aksan, Nurul Izzah (QAULAN: Journal of Islamic Communication, 2022)
Writing articles using qualitative methods of content analysis. Data collection techniques were carried out through literature research in the form of books, scientific journals, theses, and theses. While the observation process is carried out on digital media and mass media, to obtain data that supports the writing of articles. This article concludes that proficiency in digital literacy is an undoubted necessity amidst the serious use of the internet by the Indonesian people, where currently there are 197 million internet users in Indonesia. This is an obligation for the government and policymakers to ensure that every nation's child can use social media and the internet in the digital era properly and wisely. Do not let us be negligent in using the digital space, thus setting aside moral values and decency and ultimately causing material and non-material harm from an economic standpoint. We believe through skills in using the internet in this digital era can change and bring progress to the nation, state and society. In this new era, there is no other decision except that Indonesia's people must have sufficient capabilities, both in number and level of skills or abilities regarding digital literacy.